Industry 4.0 implications in logistics: an overview - Barreto, L. (2017)
During the last decade, the use and evolution of Information and Communication Technologies (ICT) in industry have become unavoidable. The emergence of the Industry Internet of Things (IIoT) promoted new challenges in logistic domain, which might require technological changes such as: high need for transparency (supply chain visibility); integrity control (right products, at the right time, place, quantity condition and at the right cost) in the supply chains. These evolvements introduce the concept of Logistics 4.0. In this paper, it is presented some reflections regarding the adequate requirements and issues enabling organizations to be efficient, and fully operational in Logistics 4.0 context.